PSII-39 Effects of electrostatic spray and natural antioxidants on sensory quality and color of grass- finished beef strip steaks - Sajeev, Dishnu (J Anim Sci, 2019)
This study was aimed to determine the effects of electrostatic spray and natural antioxidants on sensory quality, color, and metmyoglobin reductase activity in grass-finished beef strip steaks. Eighteen certified grass-finished beef loins from nine animals were purchased from a certified grass-fed beef purveyor. Each loin was cut into eight 2.5-cm thick steaks without the gluteus medius muscle. A factorial arrangement of four treatments including a negative control (no spraying; NEG) and 1000-ppm of electrostatic spray of cherry extract rich in ascorbic acid (ES-ACE), electrostatic spray of rosemary and green tea extract rich in polyphenols (ES-RGT), and pressurized spray of ACE (PS-ACE) at 2 retail time points (0 and 5 d) was randomized within an animal. Instrumental color (CIE L*, a*, b*) and reflectance spectra (400 to 700 nm) were measured d-5 steaks. Five loins were randomly selected for metmyoglobin reductase activity and the other four loins were used for sensory evaluation. On d 0, ES_ACE steaks were slightly darker than ES_RGT and NEG steaks (P < 0.022); however, these differences disappeared on d 5 (P ≥ 0.138). On d 0, redness of ES_RGT and NEG steaks were greater than that of ES_ACE and PS_ACE steaks (P < 0.002); however, both ES_ACE and PS_ ACE steaks had more redness than ES_RGT and NEG steaks (P < 0.002). Similar phenomenon was found for color saturation. Both ES_ACE and PS_ACE steaks had less metmyoglobin and more oxymyoglobin than ES_RGT and NEG steaks on d 5 (P ≤ 0.021). All steaks had more sourness, bloody, and oxidized off-flavors on d 5 than d 0 (P ≤ 0.017). Electrostatic and pressurized spray provided similar protection for color stability and sensory quality; however, the natural antioxidant rich in ascorbic acid was more effective than polyphenol-rich natural extract.